Potential for water savings & reuse in the Arab Region - Abu-Zeid K.; Abdel-Megeed A.; Elbadawy O. (Water management for drought mitigation in the Mediterranean, 2004)
Water resources scarcity, accessibility, and environmental degradation are the major challenges facing most of the Arab countries. Realizing the scarcity of water and the inaccessibility to water services in many parts of the Arab region, in addition to the large amount of investments needed in the water sector, water savings and reuse will play a very important role in development in the Arab region. This paper presents water savings methods in the different water sectors; estimates the current annual potential for water savings in the Arab region at 20 Billion Cubic Meters (BCM) per year in the irrigation, domestic, and industrial sectors. The paper also estimates the potential for wastewater reuse and recycling of domestic and industrial water in the Arab region at 12 BCM/year, which is considered an alternative non-conventional water resource that will indirectly contribute to water savings. The paper also gives assessments of expected future water savings that could be realized if water savings measures are put in place, and it gives estimates of the associated costs for implementing most of these water savings measures.
Special Session on 'Water Management for Drought Mitigation in the Mediterranean' at the Regional Conference on Arab Water 2004, 2004/04/12-16, Cairo (Egypt)